Cyberpunk : edgerunners madness. 1 - Sztybor, Bartosz (Cyberpunk : Edgerunners madness, 2026)
An action-packed manga prequel to the hit Netflix anime series, Cyberpunk: Edgerunners, featuring fan-favorite characters Rebecca and Pilar! Rebecca and her big brother Pilar pursue their dream of becoming a legendary edgerunner just like their father. And in Night City, where violence, greed, and corruption run rampant, they'll have to abandon who they once were and dive headlong into the mayhem, where they'll struggle, suffer, and sow chaos everywhere they go! But when a mysterious man appears, the trajectory of their future takes a turn. Witness pure madness as they rush through Night City to prove themselves as edgerunners!